2021
DOI: 10.1002/cctc.202001748
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Metal‐Support Interactions between Ruthenium and Nanodiamond‐derived Carbon material for CO Oxidation

Abstract: For supported metal catalysts, metal‐support interactions (MSI) are vital for their catalytic performance, which can be regulated by controlling surface structures of supports. In this work, two kinds of nanodiamond (ND)‐derived carbon materials, i. e. ND@graphene (ND@G) and onion‐like carbon (OLC), were applied to support Ru catalyst. The characterization results show that compared with OLC supported Ru catalyst (Ru/OLC), ND@G supported Ru catalyst (Ru/ND@G) exhibits a higher Ru dispersity, large amount of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This may result from that the defects and the curvature of the graphite carbon layers can promote electron localization and increase the surface electron density. 50,51 It has been demonstrated that if the Fermi levels of the metal and carbon supports are different, an electron transfer occurs when the metal-support interface is created to shift the local Paper NJC work function at the catalytic outer surface. 27 This electronic transfer results from the formation of polar bonds with more or less ionic characters between the carbon support surface atoms and the metal atoms.…”
Section: Catalytic Performance Of Levulinic Acid Hydrogenationmentioning
confidence: 99%
“…This may result from that the defects and the curvature of the graphite carbon layers can promote electron localization and increase the surface electron density. 50,51 It has been demonstrated that if the Fermi levels of the metal and carbon supports are different, an electron transfer occurs when the metal-support interface is created to shift the local Paper NJC work function at the catalytic outer surface. 27 This electronic transfer results from the formation of polar bonds with more or less ionic characters between the carbon support surface atoms and the metal atoms.…”
Section: Catalytic Performance Of Levulinic Acid Hydrogenationmentioning
confidence: 99%